Traditional sheep breeding practices under agroforestry system of Gedeo zone, Southern Ethiopia. - Biruh Tesfahun Tezera; Demeke Haile Engidashet (PLoS ONE)
The study was undertaken in Gedeo zone with the aim to identify traditional sheep breeding practices. Three potential districts (Yirgachefe, Bule and Gedeb) were purposely selected from Gedeo zone. A total of 180 smallholder sheep farmers were selected at random to complete a structured questionnaire that had been pretested. A pairwise ranking tool was used to prioritize ranked data during focus group discussion. Descriptive statistics were generated using SPSS version 26, while indices were computed for the ranked data. Mating happens because most farmers in Gedeo zone (80%) own breeding rams that are mixed and run with ewe flocks. Fifty-two percent of farmers were certain that their breeding rams mate with neighboring ewes. Nearly 70% of farmers prevented unwanted sheep breeding in their flocks by castrating or isolating undesirable rams from the ewe flock. Undesired or old breeding rams were replaced either from the same flock (58.9%) or purchased from local markets (41.1%). Breeding flock selection was common in Gedeo zone, with 97.2% of farmers selecting breeding rams and 93.3% of farmers selecting breeding ewes. Genotype (Index = 0.26) and body conformation (Index = 0.20) were the primary and secondary criteria used to select breeding ewes. Likewise, confirmation (Index = 0.25), genotype (Index = 0.24) and lamb growth rate (Index = 0.19) were the top three criteria when selecting breeding rams. Approximately three-quarters of interviewed farmers culled sheep due to poor body condition (31.8%), old age (28.6%), sickness (22.7%) and sterility (15.6%). Castration of rams was more common in Gedeb (58.3%) and Yirgachefe (55%) districts, and it was done for fattening, controlling unwanted breeding, and improving temperament. The mean selection and castration age of breeding rams were 13.18 and 30.72 months. In general, sheep breeding strategies for Gedeo zone should take into account section preferences and basic traditional sheep breeding practices.